Titus Flavius Clemens’ Stance on Wine as Expressed in Paedagogus - Dybała, Jolanta; Jagusiak, Krzysztof; Pawlak, Michał (Studia Ceranea, 2019)
Titus Flavius Clemens was a philosopher and Christian theologian from the period of the 2nd–3th century. The aim of this paper is to present his view on the subject of wine and his recommendations on wine consumption as described in his work entitled Paedagogus. In this work Titus Flavius Clemens focuses primarily on the moral side of drinking wine. He is a great supporter of the ancient principle of moderation, or the golden mean (μεσότης). We also find its traces in his recommendations regarding the drinking of wine. First of all, he does not require Christians to be abstinent. Although he considers water as the best natural beverage to satisfy thirst, he does not make them reject God’s wine. The only condition he sets, however, is to maintain moderation in drinking it. He recommends diluting wine with water, as the peaceful Greeks always did, unlike the war-loving barbarians who were more prone to drunkenness. On the other hand, Titus Flavius Clemens warns the reader against excessive dilution of wine, so that it does not turn out to be pure water. He severely criticizes drunkenness, picturesquely presenting the behavior of drunks, both men and women. Wine in moderation has, in his opinion, its advantages – social, familial and individual. It makes a person better disposed to himself or herself, kinder to friends and more gentle to family members. Wine, when consumed in moderation, may also have medicinal properties. Clemens is well aware of this fact and in his work he cites several medical opinions on the subject. Unfortunately, in Paedagogus we find little information about wine as a food product / as an everyday bevarage. The input on the subject is limited to the list of exclusive, imported wines. What is worth noting, Titus Flavius Clemens appears to be a sommelier in this way.